2008
DOI: 10.1111/j.1349-7006.2007.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor mutation, but not sex and smoking, is independently associated with favorable prognosis of gefitinib‐treated patients with lung adenocarcinoma

Abstract: Epidermal growth factor receptor (EGFR) mutations have been reported as a predictive factor for favorable prognosis of gefitinibtreated patients with lung adenocarcinoma. However, its confounding with sex and smoking makes it unclear whether the EGFR mutation is independently associated with prolonged patient survival. In this study, we analyzed a large-scale database to discriminate the survival impact of EGFR mutations against those of sex and smoking after gefitinib therapy. EGFR mutations in exon19 and exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…Several recent papers have suggested that tumor molecular profiling may supersede these clinical selection factors for EGFR-TKI treatment in patients with NSCLC. Toyooka et al reported that EGFR mutation was independently associated with a favorable prognosis in gefitinibtreated patients regardless of gender or smoking history (6). In the present case, EGFR mutation was detected in a male, currently smoking, SCC patient, indicating that EGFR mutational analysis is more important than clinical characteristics and histology.…”
Section: Discussionmentioning
confidence: 47%
“…Several recent papers have suggested that tumor molecular profiling may supersede these clinical selection factors for EGFR-TKI treatment in patients with NSCLC. Toyooka et al reported that EGFR mutation was independently associated with a favorable prognosis in gefitinibtreated patients regardless of gender or smoking history (6). In the present case, EGFR mutation was detected in a male, currently smoking, SCC patient, indicating that EGFR mutational analysis is more important than clinical characteristics and histology.…”
Section: Discussionmentioning
confidence: 47%
“…In EGFR-mutant cases, EGFR-TKIs would be expected to be effective and long-term survival could be expected with local treatment of cases of localized recurrence, such as cases 3 and 6 in Table VI. Our study demonstrated that bilateral/contralateral lung recurrence was significantly more frequent among EGFR+ cases. In those cases, long-term survival may be achieved with combination therapy, consisting of EGFR-TKI treatment, cytotoxic chemotherapy and local treatment, for each lesion (21)(22)(23)(24). In general, long post-recurrence survival may be expected in patients with slow-growing tumors or long recurrence-free survival; however, no association between post-recurrence survival time and recurrence-free survival time according to EGFR mutations was observed in this study.…”
Section: Discussionmentioning
confidence: 59%
“…EGFR mutations have been reported as a predictive factor for favorable prognosis of gefitinib-treated patients with lung ADC. Patient's sex and smoking status were not significantly associated with longer overall survival and progression-free survival according to EGFR mutation status [26]. Patients with advanced NSCLC who were selected on the basis of EGFR mutations improved progression-free survival with acceptable toxicity but those with no EGFR mutation did not.…”
Section: Discussionmentioning
confidence: 86%